Insights Into Genome-Wide Association Study for Diabetes: A Bibliometric and Visual Analysis From 2001 to 2021 - Liu, Yang; Wang, Yun; Qin, Shan; Jin, Xinye; Jin, Lingzi; Gu, Weijun; Mu, Yiming (Frontiers in Endocrinology, 2022)
Hundreds of research and review articles have been published in the last two decades concerning genome-wide association study (GWAS) in diabetes. We aimed to evaluate the hotspots and future trends in GWAS in diabetes research through bibliometric analysis. Accordingly, 567 research and review articles published between 2001 and 2021 were included. A rising trend was noted in the annual number of publications and citations on GWAS in diabetes during this period. The Harvard University and the Harvard Medical School have played leading roles in genome research. Hotspot analyses indicated that DNA methylation and genetic variation, especially in type-2 diabetes mellitus, are likely to remain the research hotspots. Moreover, the identification of genetic phenotypes associated with adiposity, metabolic memory, pancreatic islet, and inflammation is the leading trend in this research field. Through this review, we have provided predictions on the main research trends in the future so as to shed light on new directions and ideas for further investigations on the genetic etiology of diabetes for prevention and treatment.